Structural connections support emotional connections: Uncinate Fasciculus microstructure is related to the ability to decode facial emotion expressions. (August 2020) - Coad, Bethany M.; Postans, Mark; Hodgetts, Carl J.; Muhlert, Nils; Graham, Kim S.; Lawrence, Andrew D.
Abstract: The Uncinate Fasciculus (UF) is an association fibre tract connecting regions in the frontal and anterior temporal lobes. UF disruption is seen in several disorders associated with impaired social behaviour, but its functional role is unclear. Here we set out to test the hypothesis that the UF is important for facial expression processing, an ability fundamental to adaptive social behaviour. In two separate experiments in healthy adults, we used high-angular resolution diffusion-weighted imaging (HARDI) and constrained spherical deconvolution (CSD) tractography to virtually dissect the UF, plus a control tract (the corticospinal tract (CST)), and quantify, via fractional anisotropy (FA), individual differences in tract microstructure. In Experiment 1, participants completed the Reading the Mind in the Eyes Task (RMET), a well-validated assay of facial expression decoding. In Experiment 2, a different set of participants completed the RMET, plus an odd-emotion-out task of facial emotion discrimination. In both experiments, participants also completed a control odd-identity-out facial identity discrimination task. In Experiment 1, FA of the right-, but not the left-hemisphere, UF was significantly correlated with performance on the RMET task, specifically for emotional, but not neutral expressions. UF FA was not significantly correlated with facial identity discrimination performance. In Experiment 2, FA of the right-, but not left-hemisphere, UF was again significantly correlated with performance on emotional items from the RMET, together with performance on the facial emotion discrimination task. Again, no significant association was found between UF FA and facial identity discrimination performance. Our findings highlight the contribution of right-hemisphere UF microstructure to inter-individual variability in the ability to decode facial emotion expressions, and may explain why disruption of this pathway affects social behaviour. Highlights: We studied white matter microstructure correlates of facial emotion decoding skills. Focused on the role of a key limbic tract, the Uncinate Fasciculus (UF). Right UF microstructure linked to facial expression decoding skills. UF microstructure not related to facial identity discrimination skills. Right UF has a distinct role in the processing of facial expressions of emotion.